Children Affected By HIV/AIDS And Human Capital Development In West Africa: A Panel Data Analysis - Dauda, Rasaki Stephen; Olaniyan, Olanrewaju (Advances in Social Sciences Research Journal, 2017)
This study investigates how the number of children infected with HIV/AIDS and AIDS-induced orphans affect human capital development in West Africa. Two panel data models were estimated, using the Fixed Effects estimation technique supported by the Hausman specification test result. The findings overwhelmingly suggest that number of children living with HIV/AIDS and AIDS-induced orphans have negative and significant effects on human capital development in West Africa. Therefore, efforts should be geared towards hurting and reversing the spread of the disease as well as eradicating it in West Africa. Care should also be provided for the education, health, nutrition, shelter and psychological needs of the affected children.